2011
DOI: 10.1111/j.1743-6109.2011.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function Assessment in Postmenopausal Women with the 14-Item Changes in Sexual Functioning Questionnaire

Abstract: Introduction Sexual function assessment is relevant to improve female health care. Aim Assess sexual function in postmenopausal women and determine predictors related to sociodemographic, lifestyle, and health-related female/partner data and tool measures. Methods Cross-sectional study in which 117 sexually active postmenopausal women filled out the 14-item C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 37 publications
0
29
0
5
Order By: Relevance
“…Various reports seem to indicate a link between general quality of life, menopausal symptoms and sexual function in middle-aged women [17][18][19] . During menopause, a decrease in libido and sexual dysfunction occurs [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various reports seem to indicate a link between general quality of life, menopausal symptoms and sexual function in middle-aged women [17][18][19] . During menopause, a decrease in libido and sexual dysfunction occurs [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…During menopause, a decrease in libido and sexual dysfunction occurs [18][19][20] . Moreover, sleep disorders, depressed mood and other psychological problems that reduce quality of life have a significant impact on female sexual function 17,21 . In a longitudinal analysis, Elavsky et al 13 found that middle-aged women perceive their body more positively when physical activity levels are high, increasing their selfesteem, and maintaining a healthy Body Mass Index (BMI).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be due to decline in hormones leading to urogenital atrophy (6) . Also due to deceased physical activity menopausal symptoms become more intense like mood, depression, anxiety, decreased sleep and musculoskeletal disorders leading to diminished quality of life (7,8,9) . Sometimes these FSDs are due to sexual pain which may be caused by PID, deep infiltrating lesions of pelvis or endometriosis which can be treated accordingly (10) .…”
Section: Introductionmentioning
confidence: 99%